Etiological Spectrum of Pancytopenia / Bicytopenia in Children 2 Months to 12 Years of Age - Muddassar Sharif , Najaf Masood , Muhammad Zahoor ul Haq , Mobina Ahsan Dodhy , Rai Muhammad Asghar (Journal of Rawalpindi Medical College, 2014)
Background: To determine the etiological spectrum of pancytopenia / bicytopenia in children aged 2 months to 12 years. Methods: In this cross sectional descriptive study patients from 2 months to 12 years of age presenting with different cytopenias were included. Demographic profile and clinical findings were noted. Degree of malnutrition was assessed according to Gomez classification. Blood complete picture and peripheral smear were carried out for every patient having pancytopenia(leucopenia, anaemia and thrombocytopenia) or bicytopenia (if only two parameters from the full blood count are low) were further subjected to bone marrow aspiration and trephine biopsy Results: A total of 105 patients were included in the study..More than half of the patients (61%) were 2 - 60 months of age . Out of these 64 patients, 71% were malnourished (second and third degree malnutrition according to Gomez classification) and it was statistically found to be significant (p value.004) . Fever (82.9%) was the commonest presentation . Inadequate dietary history was present in 51.4%. About half of the patients (56.2%) received blood transfusion before bone marrow examination .Forty eight (36.3 %) patients had features of infection at presentation. Pneumonia was the leading cause of infection. Hepatosplenomegaly was seen in 27.6% and isolated splenomegaly in 4.8%, while 5.7% had generalized lymphadenopathy. Severe anemia (Hemoglobin < 5gm %) was found in 25.7%, leucopenia (TLC < 4000/cmm) in 45.7%, severe thrombocytopenia (platelet count ≤ 20,000/cmm) in 31.4%. Approximately half of the patients (62.9%) had bicytopenia and 37.1% had pancytopenia on blood complete picture . More than one third(41.9%) patients were diagnosed. Megaloblastic anemia on bone marrow examination and it was the leading cause of bicytopenia / pancytopenia in patients aged 13-60 months. Out of 40 patients of this age group 20 had Megaloblastic anemia and 18 out of these 20 patients (90%) were with grade II – III malnutrition (p valve 0.02) .Infective etiology was the cause of bicytopenia / pancytopenia in 19%, aplastic anemia in 13.3% and acute leukemia in 10.5% patients. Conclusion: Megaloblastic anemia was the commonest cause of pancytopenia / bicytopenia followed by infective etiology, aplastic anemia and acute leukemia. Malnutrition was seen in majority of patients with megaloblastic anaemia